2018
DOI: 10.1007/s00439-018-1875-2
|View full text |Cite
|
Sign up to set email alerts
|

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies

Abstract: GJA8 encodes connexin 50 (Cx50), a transmembrane protein involved in the formation of lens gap junctions. GJA8 mutations have been linked to early onset cataracts in humans and animal models. In mice, missense mutations and homozygous Gja8 deletions lead to smaller lenses and microphthalmia in addition to cataract, suggesting that Gja8 may play a role in both lens development and ocular growth. Following screening of GJA8 in a cohort of 426 individuals with severe congenital eye anomalies, primarily anophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 69 publications
0
33
0
Order By: Relevance
“…To investigate further the role of GJA8 in A/M, Ceroni et al (Ceroni et al 2018) analyzed a large cohort of individuals presenting with a wide range of developmental eye anomalies, mainly A/M and coloboma. This study identified 6 likely pathogenic sequence variants in 7 independent families, including the variant previously reported by Ma et al (Ma et al 2016).…”
Section: Gja8 (Gap Junction Protein Alpha 8)mentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate further the role of GJA8 in A/M, Ceroni et al (Ceroni et al 2018) analyzed a large cohort of individuals presenting with a wide range of developmental eye anomalies, mainly A/M and coloboma. This study identified 6 likely pathogenic sequence variants in 7 independent families, including the variant previously reported by Ma et al (Ma et al 2016).…”
Section: Gja8 (Gap Junction Protein Alpha 8)mentioning
confidence: 99%
“…Interestingly, in all 6 families where segregation analysis could be performed, these variants co-segregated with both early onset cataracts and microphthalmia, supporting the hypothesis that the gene may be involved a broader range of human developmental eye anomalies. The missense variant p.(Gly94Arg) (c.280G>A, NM_005267.4) for which segregation analysis could not be performed was identified in a child with congenital aphakia, sclerocornea, microphthalmia and coloboma (Ceroni et al 2018) (Fig. 3b,c).…”
Section: Gja8 (Gap Junction Protein Alpha 8)mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, 90 heterozygous variants have been described in families with autosomal-dominant cataract, and a single homozygous variant in autosomalrecessive cataract has been found in GJA8, associated not only with inherited cataract but also age-related cataract and other eye anomalies including microcornea, microphthalmia and corneal opacification. 37…”
Section: Membrane Proteins Connexinsmentioning
confidence: 99%
“…In humans, a subpopulation of colobomata is a result of mutations in developmentally important genes, however, the origins for many OF closure defects are unknown (for reviews, see (3,7,8,13,14)). Additional genes have been identified in animal models; substantial progress has been made in understanding critical processes, including growth and patterning of the ventral optic cup and optic nerve head (15- 19), cell-cell contact and signaling (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), crosstalk with migrating hyaloid precursors and extracellular matrix components (31)(32)(33)(34)(35)(36), cytoskeleton dynamics (37,38), epigenetics (39), degradation of ECM and cellular proteins (40)(41)(42), programmed cell death, survival and cell proliferation (43,44) (for reviews, see (7,8,13)). Elegant in vivo imaging studies in zebrafish and excellent anatomical analyses in chick have characterized important morphogenetic and cellular behavior (20,27,34,(45)(46)(47)(48)(49).…”
Section: Introductionmentioning
confidence: 99%